2009
DOI: 10.1590/s1413-78522009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Evolução funcional nas fraturas da extremidade proximal do fêmur

Abstract: Objectives: To assess the functional capacity evolution and the physiologic score in patients with proximal femoral end fractures, as well as to compare the final results of the treatment provided to the several pre-fracture variables. Materials and Methods: A prospective study with patients over 40 years old diagnosed with proximal femoral fracture. The patients were submitted to a pre-established protocol and followed up on an outpatient basis for a period of one year. Results: 68 patients were assessed (27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
2
10
0
13
Order By: Relevance
“…This is in line with the epidemiological profile of osteoporosis and its clinical manifestation of fractures of the proximal femur, which is proportionally greater among white postmenopausal women (3,(9)(10)(11)(12) . With regard to gender, there was no difference in the survival curve over the course of time.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is in line with the epidemiological profile of osteoporosis and its clinical manifestation of fractures of the proximal femur, which is proportionally greater among white postmenopausal women (3,(9)(10)(11)(12) . With regard to gender, there was no difference in the survival curve over the course of time.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, elderly people are much more subject to complications, both during the immediate postoperative period and later on (8) . Studies in developed countries have suggested that certain preoperative factors are associated with higher mortality rates among patients presenting hip fractures on admission, for example: nonwhite color (3,(9)(10)(11)(12) , advanced age (11,(13)(14)(15) , presence of dementia (16)(17)(18) , male sex (13,19,20) , clinical comorbidities (11,14,16,21,22) and delirium (18,23,24) . In view of the importance that fractures of the proximal femur have for society, our aim was to determine the mortality rate and preoperative factors related …”
Section: Introductionmentioning
confidence: 99%
“…18 In a prospective study of 68 patients, only 32.56% reacquired the walking capacity and 27.9% of the previously independent patients needed special care. 7 As a condition of high prevalence among the elderly, whose treatment is essentially surgery 5 and a long hospital stay, femoral fracture entails high costs. In the triennium 2006-2008, femur fracture accounted for 2% of the expenditures of all hospitalizations in the elderly over 60 years in Brazil, and cost approximately R$ 120 million.…”
Section: Resultsmentioning
confidence: 99%
“…6 In addition to high mortality, femoral fracture also presents a high morbidity rate and functional impairment, causing a psychosocial impact with the degree of post-fracture dependence, reaching 30%. 7,8 Total expenditures on hospitalization for femoral fractures in the elderly in Brazil were around 40 million R$ per year in the threeyear period of 2006-2008, representing about 2% of all causes of hospitalization among the elderly. 9 Driven by the absence of data on osteoporotic femoral fractures in the State of Paraná and the need to know the magnitude of the problem and its costs to the public health care system (SUS), the present study aims to assess the incidence and economic impact that this morbidity represented for the state in the period from January 2010 to December 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of any of these factors, the indication is for conservative treatment. The objective of surgical treatment is to prevent the progression of functional incapacity and to restore the function of the limb so that it is similar to the pre-fracture status [12]. That said, the elderly in the post-operative period remain unable to walk without supporting the operated limb, and their rehabilitation can be influenced by their clinical conditions, the success of the treatment and of the rehabilitation process.…”
Section: Introductionmentioning
confidence: 99%